Short-Term Training Courses in Library and Information Science in India - Kamath, V. A. (Journal of Information and Knowledge, 1978)
Highlights the growth in Information Science Education. Points out the need for short-term courses in Library and Information Science. Lists various short term courses conducted in 1970's in India and identifies five main categories of short-term courses. Suggests areas for co-operation in conducting short-term courses.